Treatment of Infectious Sacroiliitis in Pregnant Patients: A Case for Surgical Debridement. Issue 3 (4th September 2021) - Vajapey, Sravya P.; Brown, Chelsea; Sullivan, Anne; Van Hoff, Corey
Abstract : Infectious sacroiliitis is a rare disease entity that can mimic other conditions. If recognized early and treated appropriately, most patients experience favorable outcomes. Pregnant patients with infectious sacroiliitis pose a unique challenge for the physician. We report 3 cases of pregnant patients with infectious sacroiliitis, describe the surgical technique used to debride the sacroiliac joint in pregnant patients, report their outcomes, and provide a treatment algorithm for management of this condition in this patient population. All patients failed initial conservative treatment with antibiotics and underwent surgical debridement. All 3 had history of intravenous drug use, which is one of the predisposing factors. All 3 patients had favorable outcomes after surgery. Surgical debridement of infectious sacroiliitis is a viable treatment option in the pregnant patient with infectious sacroiliitis resistant to conservative treatment.